123k views
5 votes
Condensing Logarithmic Expressions In Exercise, use the properties of logarithms to rewrite the expression as the logarithm of a single quantity.

In(2x + 5) = In(x - 3)

2 Answers

3 votes

Simplify the logarithm.

In(2x + 5) = In(x - 3) → In(2x + 5) - In(x - 3) = 0

Use the quotient rule [
\text{ln}(a)/(b) = \text{ln(a)}-\text{ln(b)} ] to simplify.

In(2x + 5) - In(x - 3) = 0 →
\frac{\text{ln(2x + 5)}}{\text{ln}(x - 3)}=0

Therefore, the logarithm as a single quantity is
\frac{\text{ln(2x + 5)}}{\text{ln}(x - 3)}=0

Best of Luck!

User Froosh
by
5.2k points
4 votes

Answer:


(\ln(2x + 5))/(\ln(x - 3)) = 0

Explanation:

Data provided in the question:

In(2x + 5) = In(x - 3)

we can rearrange the above equation as

⇒ In(2x + 5) - In(x - 3) = 0

now,

from the properties of natural log function, we know that


\ln((A)/(B)) = \ln(A)-\ln(B)

therefore,

we get


(\ln(2x + 5))/(\ln(x - 3)) = 0

Hence,

Expression as the logarithm of a single quantity is
(\ln(2x + 5))/(\ln(x - 3)) = 0

User Mlangenberg
by
5.3k points